PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN KIMIA DAN FARMASI DI INDONESIA - Henny Setyo Lestari; Dhetoriana Permatasari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2009)
This research is aimed to determine the influence of corporate governance on firm pe ormance. The sample used were 16 companies, which is divided into 8 companies in hemical sector and 8 companies in pharmaceutical, that are listed in Indonesia Stock Exchange during the period of 2004 to 2008, which were selected using purposive sa pling method. Corporate governance in this research was measured with board size , board independence, and ownership concentration While firm performance was To sured by ROA and ROE. Menthods of data analysis were using multiple regressionfacility. Based on the results of this research showed that there was no significant .1influence between corporate governance (board size, board independence, andownership concentration) on firm performance (ROA and ROE).Keywords : Corporate Governance and firm performance